Rumpelstiltskin - N/A (Mind to mind)
A miller$1 (Bs daughter is forced to spin straw into gold. A strange little man helps her in exchange for promises. She later guesses his name$1 (BRumpelstiltskin$1 (Bto save her child, and he disappears.s
Keywords: English